Teaching self-regulation through role modeling in K-12 - Adıgüzel, Tufan; Aşık, Gürsu; Bulut, Mehmet Akın; Kaya, Mehmet Haldun; Özel, Serkan (Frontiers in Education, 2023)
For K-12 teachers to develop effective teaching skills, integration of role modeling strategies into teaching and learning process as a dimension of selfregulated learning is of the foremost value. Role modeling strategy training through a hybrid professional development model bears the potential to serve as a facilitating component in promoting K-12 teachers’ instructional competence. Conducted within the self-regulated learning framework, this study suggested findings of a teacher professional development training aimed at role modeling strategy implementation at K-12 level. Pursuing a mixed-method model, the current research was performed with 16 teachers who were trained and supervised to integrate role-modeling strategies into their teaching context. In this study, the data sources were role-modeling- integrated lesson plans, trainers’ feedback on these lesson plans, and online student products. The data collection methods included lesson plan evaluation through a role-modeling rubric in a quantitative fashion, whereas content analysis of trainer feedback on lesson plans, latterly revised lesson plans and online student products composed the qualitative aspect. Results revealed that this professional development training achieved significantly positive changes in teachers’ role modeling strategy implementation skills, particularly in terms of teachers’ role as agents in students’ self-regulated learning skills, promotion of student-centered learning and overall improvement in students’ self-regulated learning skills. Further, the integration of education technology tools into lessons was observed to have a positive impact on enhancing students’ self-regulated learning skills. This study could offer major contributions to designing teacher professional development training for researchers, practitioners, and teacher trainers, particularly in role modeling dimension of self-regulated learning.